Novel sustainable evaluation approach for multi-biomass supply chain - How, Bing Shen (2018)
After the oil crisis held in 1973 and 1979, academicians and industry players have noticed the importance and necessity of having alternative and sustainable energy sources in future. Biological wastes, also named as “Biomass” has been cited as one of the significant sustainable energy sources. Biomass poses an ideal and substantial potential to achieve a sustainable system. However, the development of biomass industry is still relatively sluggish due to the lack of confidence of the investor to venture in this relatively new green business. This is most probably attributed to the low-maturation of biomass technologies compared to other conventional technologies, high logistics cost required for biomass transportation and uncertain market penetration barrier for the biomass-derived products. This raises the importance of having a proper biomass management system and a systematic evaluation approach to assess the sustainability performances of the biomass industry.